A tool for identifying post-Intervention value shifts in urban heritage places: the Heritage Value Circle. Issue 1 (2nd January 2022) - Özçakır, Özgün; Bilgin Altınöz, A. Güliz; Mignosa, Anna
ABSTRACT: Heritage places become the focus of interventions due to their socio-cultural and economic values, but as value assessments are subjective, these values can be interpreted differently by decision-makers when considering interventions. Different interpretations of values may result in different interventions, leading to the transformation of the physical, social, and economic features of urban heritage places, and consequently, to changes in their socio-cultural and economic values. Identifying value shifts can help in the recognition of the impact of interventions on the preservation, and thus sustainability, of heritage places. Considering the contemporary debates around the issue of sustainability, this study aims to identify the link between impact assessments and sustainable development by answering the following question: 'How can post-intervention value shifts be identified to assess the impact of the intervention on the sustainability of heritage places?' To answer this question, the study introduces a qualitative impact assessment tool: the Heritage Value Circle (HVC), which is based on the examination of urban interventions in different contexts, and a content analysis of the policy documents related to heritage conservation of various NGOs and IGOs. The study identifies seven components of interventions and defines correlation between interventions, pillars of sustainability and values.